Morphing structures and fatigue: The case of an unmanned aerial vehicle wing leading edge. Issue 10 (12th July 2017) - Moreira, S.J.; Tavares, S.M.O.; de Castro, P.M.S.T.
Abstract: With the emergence of novel aircraft structural concepts, which make use of large‐scale shape deflections to achieve improved flight performance across significantly different flight regimes and missions, unusual crack paths and mixed‐mode crack propagation situations may take place. Consequently, morphing concepts require a full understanding of the materials' behaviour in primary or secondary structures to reliably withstand unusual and demanding operating conditions. A case study of a morphing leading edge developed for the wings of an unmanned aerial vehicle is presented in this paper. Leading edges are subjected to damage originated by bird strike or other events, and those damages can compromise the structural integrity and stability of the flight. Due to the deflections during the morphing structure actuation, cracks will propagate eventually until critical sizes. Possible crack propagation scenarios are presented, considering the service operation of the morphing leading edge.